Dynamics of China-Pakistan Strategic Partnership and its Impact on India - Azeem Gul; Riaz Ahmad; Muhammad Adeel Khan, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
The cooperation between China and Pakistan which was mostly dominated in the defense sector in the pas5 has now transformed into another area of economic interdependence where Pakistan decided to become an important part of China’s flagship programs such as China-PakistanEconomic-Corridor (CPEC). Most of the academic attention on the topic has covered by exploring China-Pakistan friendship which is centered on CPEC and defense cooperation without giving this topic a conceptual understanding of strategic partnership along with theoretical context. Against this backdrop, the current study is unique by adding the current literature a conceptual understating of strategic partnership and its application in the study along with adhering to the application of theoretical construct. The study also shows the cause and effect relationship of two variables i.e. China-Pakistan as independent variable and implications for India and its counterstrategies as dependent variable. CPEC provides a new model of cooperation of China with other South Asian states which have drifted them towards China’s orbit of influence. All these developments have created concerns in India where experts have believed that its influence has been minimized in the region. On its part, India is taking measures to contain China’s rise by approaching to new policies at the political, military, and economic level.